Evaluating The Quality Of Banking Services In The Private Banks Operating In Lattakia Governorate - مرهج منذر; ديـب رنا (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The research aimed to evaluate the quality of banking services in private banks operating in Lattakia Governorate from the point of view of clients through five dimensions, namely after embodiment (the bank’s readiness of equipment), after reliability (the bank performed well in its business), and the response dimension (the bank’s response to the service with high quality. After security (customer confidence in the bank and the quality of the provided banking service), and after sympathy (concern for individual and personal variables of the client), the researcher used the descriptive and analytical approach by reviewing literature and previous studies to prepare the study questionnaire with the aim of studying the research vocabulary and compiling and collecting the field information needed for the research topic 386 questionnaires were distributed, and then unpacked and analyzed using the SPSS statistical program, and the appropriate statistical tests were used in order to reach valuable indications and indicators that support the subject of the study, and it reached the most important results of the following: Private banks enjoy the quality of banking services in its fifth dimensions (embodiment, reliability, response, Security, sympathy) from the viewpoint of the respondents. However, the response dimension is less available in private banks, followed by accreditation. Friendly, and then after sympathy, and then after safety, while the embodiment dimension is more available in private banks from the viewpoint of the sample members..